EFFECT OF FOLIAR APPLICATION SALICYLIC ACID ON CITRUS ROOTSTOCKS TOLERANCE TO SOIL SALINITY - & et al., Al-hayany (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This experiment was carried out at the private nursery located at Baquba city/ Diyala governorate during 2015 agricultural season on three years old Citrus rootstocks seedlings to study the effect foliar application of salicylic acid on seedlings tolerance to soil salinity. The experiment included 24 treatment represented three factors: soil salinity levels (1.14,4.62 and 5.30 dSm-1) , two levels of salicylic acid (0 and 250 mg.l -1) and four citrus rootstocks (Sour orange, Cleopatra mandarin, Volkamariana lemon and Troyercitrange ),and their interactions with three replications . The results showed that: increasing soil salinity reduced most studied growth parameters (number and length of branches, number of leaves and fresh weight of the vegetative and root system). Salicylic acid application caused an increment in number of leaves, fresh and dry weight of root system. Citrus rootstocks Troyercitrange was superior on other rootstocks by giving highest values branches length, whereas Cleopatra mandarin rootstock was superior in the number of leaves.